1996
DOI: 10.1021/bi9530189
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor Binding Site for the Methyltransferase of Bacterial Chemotaxis Is Distinct from the Sites of Methylation

Abstract: The principal locus for binding interactions between the aspartate and serine receptors of escherichia coli and the methyltransferase was found to be in the last five amino acids of the receptor. The thermodynamic parameters of transferase-receptor interactions were determined by isothermal titration calorimetry. the serine receptor and three C-terminal fragments (C-fragments) of the aspartate receptor consisting of ether the last 297, 88, or 38 amino acids gave comparable values for binding (n=1, deltaH appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
225
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(237 citation statements)
references
References 60 publications
11
225
1
Order By: Relevance
“…Conformational signals in the kinase control module are transmitted by rearrangements of helix-helix contacts at the subunit interface (see text for details). The carboxyl terminus of some receptors carries a conserved pentapeptide sequence (NWETF or NWESF in the single-letter amino acid code) that interacts with the two enzymes of adaptational modification (CheR and CheB) and enhances the rates of the reactions they catalyze [69,70].…”
Section: Box 3 Functional Architecture Of the Chemoreceptor Dimermentioning
confidence: 99%
See 1 more Smart Citation
“…Conformational signals in the kinase control module are transmitted by rearrangements of helix-helix contacts at the subunit interface (see text for details). The carboxyl terminus of some receptors carries a conserved pentapeptide sequence (NWETF or NWESF in the single-letter amino acid code) that interacts with the two enzymes of adaptational modification (CheR and CheB) and enhances the rates of the reactions they catalyze [69,70].…”
Section: Box 3 Functional Architecture Of the Chemoreceptor Dimermentioning
confidence: 99%
“…Conformational signals in the kinase control module are transmitted by rearrangements of helix-helix contacts at the subunit interface (see text for details). The carboxyl terminus of some receptors carries a conserved pentapeptide sequence (NWETF or NWESF in the single-letter amino acid code) that interacts with the two enzymes of adaptational modification (CheR and CheB) and enhances the rates of the reactions they catalyze [69,70].The sequence and 3D structure of kinase control modules are conserved across the diversity of bacteria and archaea [7]. Sequence conservation is more subtle among HAMP modules [42,45] but 3D structure is probably shared for the approximately two-thirds of all chemoreceptors that contain the module [43].…”
mentioning
confidence: 99%
“…Finally, recent biochemical studies have revealed evidence of limited cooperative interactions between chemotaxis receptors during kinase regulation, and chemoreceptors are known to cluster at the poles of E. coli in living cells [53,54,55••,65••,66••]. Such clustering is critical to the adaptation of certain receptors that lack the C-terminal docking site for adaptation enzymes that is present on other receptors, including the aspartate and serine receptors [67][68][69]. It is not yet clear, however, whether clustering plays an important role in transmembrane kinase regulation.…”
Section: Remaining Structural and Mechanistic Questionsmentioning
confidence: 99%
“…The use of Phe as an anchor is not unique to CheY-CheZ C recognition in bacterial chemotaxis. The pentapeptide motif (NWETF) present at the C termini of high-copy-number E. coli methylaccepting proteins (Tar and Tsr) also uses the C-terminal Phe to tether methyltransferase CheR for methylation (50).…”
Section: Discussionmentioning
confidence: 99%